Analisis Keinternasionalan Jurnal-Jurnal Keislaman PTKI - Syarifudin, Faisal (STAIN Ponorogo, 2018)
The internationality of Al Jamiah, Studia Islamika and Journal of Indonesian Islam were analyzed based on country distribution of editors, country distribution of authors, international authors collaboration and international citation. A total of 240 articles were analyzed: 86 from al-Jamiah, 74 from Studia Islamika, and 80 from JII during the period of 2012-2016. For country distribution editors and authors, the three journals use editors from different countries which internationally represent Asia, Europe, America and Australia, where most of the editors come from Indonesia. Therefore, the contribution of global scholarship still has not reached 50% of each edition. Based on international collaboration, Al Jamiah published a little number of articles from collaboration by Indonesian and overseas authors, while Studia Islamika and Journal of Indonesian Islam had no contribution from international collaboration. International citation for all three journals are in balance during five years. They have not been much cited by authors who publish their writing globally. However, the citation may increase if international journals that cited them publish their latest edition in the future.